(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Western part of Thar desert comprises of several minerals. Bikaner district is rich in deposits ofnon metallic type of minerals like gypsum , Fuller’s Earth, Lignite, Glass sand , rock salt and clay .Thegeology of the area shows that the oldest rock encounter at shallow depth are referable to the Trans-Aravalli-Vindhyan of western Rajasthan. Aravalli-Vindhyan are the Tertiary sediments which includePalana formation of sandstone and shale with lignite.